WORD ORIGIN HELPS EXPAND LEARNERS’ VOCABULARY: A VOCABULARY TEACHING APPROACH - Jing, Li (English Review: Journal of English Education, 2015)
Abstract: This paper discussed a small part of word origin and how understanding the origin of words that can help students expand their vocabulary. Teaching or learning word origin is really an effective way to promote efï¬ciency in vocabulary expansion. Word origin (motivation) deals with the connection between name and sense, explaining how a word originated. With the knowledge of how words are originated, learners can grasp a word easier and thus expand their vocabulary more quickly. The introduction to word origin (motivation) by teachers can also help the learners gain interest in the process of learning and learn more about the cultural and historical background of the English-speaking countries. This paper tries to clarify this method of teaching from four aspects: onomatopoeia, word formation, cultural and historical background and cognitive linguistics. Keywords: word origin (motivation), vocabulary, word formation, onomatopoeia, cognitive linguistics.